A new geophilid centipede of the genus Eurytion Attems, 1903 from north-western Argentina (Chilopoda: Geophilomorpha: Geophilidae) - Pereira, Luis A. (Zootaxa, 2005)
Eurytion yungarum n. sp. (Chilopoda: Geophilomorpha: Geophilidae) is described from a specimen collected in north-western Argentina (Jujuy: some 50 Km to the west of Fraile Pintado) in the Biogeographical Province of the Yungas. The new species seems to be closely related to Eurytion lethifer Crabill, 1968 from Peru (Cuzco: Urubamba), in the same Biogeographical Province, from which it differentiates mostly in the shape of labrum; pilosity of clypeal area; chaetotaxy of walking legs; body length; number of pairs of legs and presence of lappets on the coxosternum of the first maxillae.